Studi Kasus Fournier Gangrene pada Laki-Laki 52 Tahun (Lembaga Pengembangan Kinerja Dosen, 2025)
Fournier gangrene (FG) is a progressive and life-threatening necrotising fasciitis that affects the perineum, perianal region, and external genitalia. FG is a rare condition with a high mortality rate, which is significantly influenced by comorbidities such as uncontrolled diabetes mellitus, which acts as a major predisposing factor. Early diagnosis and aggressive management, particularly surgical debridement, are key to improving patient outcomes. This study is a case report aimed at describing the clinical findings, management, and final outcome in one patient diagnosed with Fournier gangrene. Data were collected from the patient's medical records after obtaining consent. A 52-year-old man with a history of uncontrolled DM presented with complaints of pain radiating from the scrotum to the lower abdomen and perineum, scrotal swelling, and fever, which developed over 5 days. A urological physical examination revealed scrotal oedema, crepitus, and necrotic skin accompanied by foul-smelling discharge. Laboratory results showed leukocytosis and hyperglycemia. The patient was diagnosed with Fournier gangrene and immediately underwent necrotomy debridement. Pharmacological management included aggressive fluid resuscitation, broad-spectrum antibiotics, and supportive therapy. The diagnosis of Fournier gangrene was established based on clinical findings of skin necrosis, crepitus, and severe pain in the genital/perineal area with uncontrolled DM as a predisposing factor. Rapid and integrated management, including aggressive surgical debridement, broad-spectrum antibiotics, and fluid resuscitation, is fundamental to successful treatment. The patient in this case report showed improvement and was discharged after 8 days of treatment.